Growing popularity and impact of food-related visual and social media content - Philip, Ms.Leena; Bali, Dr Aasita (CENTRAL ASIA AND THE CAUCASUS, 2022)
Food is not only seen as a basic necessity, but is also being seen as a way of lifestyle. It is now not only made and eaten, but also watched. This research attempts to study the increase in the growth of viewership as well as production of food/culinary related content. The paper also analyses the impact of the Covid-19 pandemic on food media. In order to find supporting data to prove the above, an online survey was conducted among those aged between 13 - 50 and above. The sample size taken for the study is 375, using convenience sampling and snowballing techniques. The results of which provide answers to why people have been watching food media increasingly. It also identifies the exact set of population who consume food media the most. The research also further examines the presence of food in the industries of film, social media, reality TV shows and OTT (Over The Top) platforms. The study ultimately proved that there is an increase in the food and culinary related content consumption as well as production. Moreover, it also highlights that the increase has been exponentially greater during and after the 2020 pandemic, as people have been more interested in the topic and are actively participating in creating it too.